Once vs Twice-Daily Administration of Inhaled Budesonide for Mild and Moderate Well Controlled Childhood Asthma - Tahir Mehmood, Wahid Ali, Qurat-Ul-Ain, Brig Nazir Ahmed Malik, Samayya Siddiqa, Rabia Waseem But (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Simplifying dose schedules may improve adherence and morbidity associated with asthma. There is limited data on the effects of once-daily budesonide treatment using a metered dosage inhaler (MDI) and a spacer on asthma symptoms and lung function in children, however. Method: This study was conducted in POF Hospital Wah Cantt Pediatrics Department between Jan 2022 to March 2022.This Study compared the impact of inhaled budesonide doses given once daily versus twice daily on asthmatic children’s symptoms, lung function, and bronchial hyperresponsiveness. This research uses a randomised, single-blind, parallel clinical trial. Budesonide was administered to individuals using an MDI at a daily dose of either 800 mg or a fractionated dose of 400 mg twice a day for 12 weeks. For the statistical analysis, we employed both independent and paired sample tests. Results: Asthma symptoms significantly decreased in both groups. However, the once-daily group considerably outperformed the twice-daily group in terms of treatment adherence, reduction in BHR, and improvement in asthma symptoms (p <0.05). No significant variations in spirometric characteristics, morning peak expiratory flow, or plasma cortisol levels were discovered between the two groups. Conclusion: It has been shown that treating symptoms and improving BHR with one daily dose of 800g of inhaled budesonide delivered by MDI + spacer is more effective than dividing it into two doses of 400g each. The differences found in this study may have resulted from patients in the once-daily group adhering to their treatment more closely. Keywords: asthma, once, twice budesonide, wheezing